Social media in disaster management: Review of the literature and future trends through bibliometric analysis - Muhammad Ashraf, Fauzi (Springer Science and Business Media B.V., 2023)
This study provides a science map on social media application in disaster management through bibliometric analysis. Citation, co-citation, and co-words analysis were applied to identify influential social media publications in disaster management, evaluate the prospective evolution of social media and disaster management themes, and predict future research streams based on social media in disaster management. 862 journal publications were retrieved from the Web of Science, with 33,758 cited references. From the co-citation analysis, 3 clusters were classified: (1) Twitter in disaster management, (2) post-disaster recovery process, and (3) information and knowledge sharing, while the co-word analysis also produced 3 clusters (1) social media communication in disaster events, (2) social media and disaster preparedness, and (3) social media and disaster recovery. Furthermore, three research streams were discussed through inductive interpretation from the three analyses performed. This study provides theoretical and practical understanding to relevant stakeholders facing disaster through social media applications.